2021
DOI: 10.1177/15330338211041453
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab–siRNA Conjugate Linked Through Cationized Gelatin Knocks Down KRAS G12C Mutation in NSCLC Sensitizing the Cells Toward Gefitinib

Abstract: Delivery of small-interfering RNA (siRNA) has been of great interest in the past decade for effective gene silencing. To overcome synthetic and regulatory challenges posed by nanoparticle-mediated siRNA delivery, antibody–siRNA conjugate (ARC) platform is emerging as a potential siRNA delivery system suitable for clinical translation. Herein, we have developed a delivery technology based on the ARC platform for stable delivery of siRNA called as Gelatin-Antibody Delivery System (GADS). In GADS, positively char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…In contrast, in the nanoparticle map of TT/PLGA@C6 NPs and CS-FA/TT/PLGA@C6 NPs, the yellow uorescence weak, and the green uorescence was dominated, indicating the escape of nanoparticles from lysosomes. It was reported that TPP escaped lysosomes quickly because its positive charge could reduce the stability of lysosomal membrane [25,32]. Our results are consistent.…”
Section: Lysosomal Escape Behaviorsupporting
confidence: 91%
“…In contrast, in the nanoparticle map of TT/PLGA@C6 NPs and CS-FA/TT/PLGA@C6 NPs, the yellow uorescence weak, and the green uorescence was dominated, indicating the escape of nanoparticles from lysosomes. It was reported that TPP escaped lysosomes quickly because its positive charge could reduce the stability of lysosomal membrane [25,32]. Our results are consistent.…”
Section: Lysosomal Escape Behaviorsupporting
confidence: 91%
“…(C) Cetuximab–cationic gelatin–specific siRNA delivery system (CTB-cGel-siRNA conjugate). 1: Cetuximab, 2: cationic gelatin, and 3: KRASG12C-specific siRNA [ 118 ].…”
Section: Reviewmentioning
confidence: 99%
“…In the cetuximab–cationic gelatin–KRASG12C-specific siRNA gelatin antibody delivery system (GADS; CTB-cGel-siRNA conjugate), positively charged gelatin had a dual role. It acted as a linker between the antibody and the siRNA and as an endosomal escape agent for efficient delivery of the siRNA in the cell cytoplasm due to its charge reversal properties ( Figure 2 , Figure 3 ) [ 118 ]. The second system composed of gefitinib-loaded gelatin-A NPs functionalized with a cetuximab-siRNA conjugate (Ab-siRNA-GelGEF NPs) also efficiently delivered stable siRNA to the cell cytoplasm in vitro and in vivo in a mouse model ( Figure 2 , Figure 3 ).…”
Section: Reviewmentioning
confidence: 99%
“…The only major limitation was inefficient endosomal escape of these ARCs. Conjugation via cationic gelatin linker of KRAS G12C -specific siRNA and Cetuximab, allowed efficient KRAS-mutant downregulation in lung cancer cells and their sensitization to the small molecule chemotherapeutic, Gefitinib[ 119 ].…”
Section: Covalent Conjugation Of Functional Molecules To Rnamentioning
confidence: 99%